IMPLEMENTASI GRI STANDARD DAN POJK NO 51/POJK.03/2017 DALAM LAPORAN KEBERLANJUTAN PERUSAHAAN BASIC MATERIALS - Puspita, Dyah Aruning; Nurul Muri’ah; Djoko Sugiono (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2024)
This study aims to determine the implementation of the GRI Standard and POJK No. 51/POJK.03/2017 in the sustainability report for the 2020-2022 period of basic materials companies listed on the Indonesia Stock Exchange (IDX). The variable in this study is the implementation of the GRI Standard and POJK No. 51 / POJK.03 / 2017 in the sustainability report. The population in this study are basic materials companies listed on the Indonesia Stock Exchange (IDX) which are on the main board of 42 companies. Samples that meet the criteria are 13 basic materials sector companies for the 2020-2022 period so that the total is 39 samples, which are selected based on certain criteria. The analysis carried out is to identify how well the GRI Standard and POJK No. 51 / POJK.03 / 2017 are applied in the sample sustainability report. The results of the analysis show that there is an increase in the disclosure score of the GRI Standard and POJK No. 51 / POJK.03 / 2017 in the sustainability reports of basic materials companies from 2020 to 2022 which indicates that from year to year the company's concern for the environment or the sustainability performance of basic materials companies has increased. The results of this study are expected to be the knowledge and consideration of investors in investing.